(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This study explores the prospective directions of market development based on the efficiency of knowledge and competency systems at the regional level. In the context of the modern knowledge-based economy, human capital, professional competencies, and innovation capacity are considered key drivers of sustainable economic growth and competitiveness. The research analyzes the role of knowledge and competency systems in shaping market development and identifies the main factors influencing their effectiveness, including education quality, innovation activity, and digital transformation. A comprehensive approach is applied to evaluate the impact of these factors on regional market performance. The findings highlight that improving knowledge and competency systems significantly enhances market efficiency, investment attractiveness, and labor productivity. Based on the results, strategic recommendations are proposed to support innovation, strengthen the linkage between education and industry, and foster a competitive and sustainable regional economy.